2020
DOI: 10.20945/2359-3997000000273
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvement of dyslipidaemia, hyperuricemia and metabolic syndrome in patients undergoing laparoscopic sleeve gastrectomy

Abstract: Objective: The aim of the study was to assess the long-term impact of laparoscopic sleeve gastrectomy (LSG) on lipid profile, uric acid level and metabolic syndrome. Materials and methods: A prospective study was performed between 2009-2014, evaluating long-term percentage of excesso body mass index loss (%EBMIL), lipid profile, uric acid level and metabolic syndrome. Results: Overall sixty subjects were followed-up. %EBMIL increased significantly, reaching a maximum (86,9 ± 6,3%) at 5 years post-LSG. Therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this study, we found that serum uric acid levels of patients with severe obesity decreased significantly 6 and 12 months after the surgery. Similarly, multiple studies have shown that bariatric surgery effectively reduced serum uric acid levels in morbidly obese patients [ 18 22 23 24 ]. Sjöström et al [ 25 ] found that, as compared to usual care, bariatric surgery also reduced uric acid levels in the long-term follow-up, 2 and 10 years after surgery of patients who underwent gastric surgery compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that serum uric acid levels of patients with severe obesity decreased significantly 6 and 12 months after the surgery. Similarly, multiple studies have shown that bariatric surgery effectively reduced serum uric acid levels in morbidly obese patients [ 18 22 23 24 ]. Sjöström et al [ 25 ] found that, as compared to usual care, bariatric surgery also reduced uric acid levels in the long-term follow-up, 2 and 10 years after surgery of patients who underwent gastric surgery compared to the control group.…”
Section: Discussionmentioning
confidence: 99%